Аналіз виконання техніко-тактичних дій юних футболістів 13-14 років різних ігрових амплуа під час гри - Крайник, Я. Б.; Мулик, В. В.; Коваль, С. С.; Федорина, Тетяна Євгеніївна (Національний педагогічний університет ім. М. П. Драгоманова, 2019)
Проведені дослідження свідчать про різні кількісні показники техніко-тактичних дій гравців різного ігрового амплуа. Так, для воротарів найбільший відсоток техніко-тактичних дій приходиться на довгі (29,8%), короткі (27,2%) та середні передачі (21,5%). Крайнім та центральним захисникам притаманне в більшій мірі виконання коротких (29,3; 28,4%), середніх (26,2; 30,8%) та довгих передач (12,6 і 17,0%) при відносно незначній кількості ведення м’яча (8,1 і 7,6%). Півзахисниками (крайнім та центральним) окрім великої кількості передач (коротких – 28,6 і 29,4%; середніх – 25,7 і 26,6%; довгих – 12,5 і 13,2%) здійснюють обводку (9,8 і 7,8%), ведення м’яча (8,0 і 8,2%) та зупинок м’яча для подальших ігрових дій (9,2 і 9,4%). Нападники переважно застосовують короткі (28,8%) і середні (25,0%) передач, а також обводку (16,2%) та ведення м’яча (9,8%). Отримані результати свідчать, що по більшості показників техніко-тактичних дій, існує достовірна різниця, яка потребує вивчення переважного застосування окремих із них у гравців різного ігрового амплуа.

The conducted studies indicate various quantitative indicators of technical and tactical actions of players of different game roles. So, for goalkeepers, the largest percentage of technical and tactical actions is in long (29.8%), short (27.2%) and medium transfers (21.5%). Extreme and central defenders are more likely to perform short (29.3; 28.4%), medium (26.2; 30.8%) and long-range transfers (12.6 and 17.0%) with a relatively small amount of reference the ball (8.1 and 7.6%). Midfielders (extreme and central), in addition to a large number of transfers (short - 28.6 and 29.4%; medium - 25.7 and 26.6%; long - 12.5 and 13.2%) stroke (9.8 and 7.8%), dribbling the ball (8.0 and 8.2%) and stopping the ball for further playing action (9.2 and 9.4%). Forwards mainly use short (28.8%) and medium (25.0%) assists, as well as stroke (16.2%) and dribbling (9.8%). The results obtained indicate that for most indicators of technical and tactical actions, there is a significant difference, which requires the study of the predominant use of some of them by players of different game roles. Improving the technical and tactical training of young footballers at the present stage requires the implementation of new, scientifically sound approaches to the construction of the training process, starting with the initial stages of many years of training. The process of training young players covers a considerable time span of several years, and this period is marked by significant physiological changes in the body of athletes associated with growth and development. According to many authors, real training of a young athlete is impossible without taking into account the patterns of the developing organism. Much attention has been paid to the development of the concept of age-related dynamics of physical qualities in the theory of child-youth sports. Modern research in the field of children's youth football draws the attention of scientists including technical and tactical.
Analysis of the technical and tactical actions of young players 13-14 years of different game roles during the game
Keywords: футбол; спорт; техніко-тактична підготовка; football; sport; technical and tactical training